Giant room temperature anomalous Hall effect and tunable topology in a ferromagnetic topological semimetal Co2MnAl - Peigang Li (Nature Portfolio, 2020)
Band topology of Weyl semimetals is usually predetermined by material parameters and can hardly be manipulated, and their transport properties appear at low temperature. Here, the authors modify the topology via a weak magnetic field and observe a giant anomalous Hall effect at room temperature.